Ketamine: old drug, a new option - Chandra, Susilo (DiscoverSys Inc., 2019)
Unique properties and recent development in the areas of clinical properties of ketamine make this agent to be popular for a long time. This anesthetic agent has wide range of indications. Many areas of clinical application of ketamine are explored in many studies. However, not many clinicians are familiar with the wide range of clinical applications of ketamine. As time passes there are many new alternative use of ketamine, a well-established anesthetic agent. The analgesic profile of ketamine is explored to have more benefits, such as postoperative pain control and as preemptive analgesia. The other aspect, which has been studied extensively, is the neuroprotective profile of ketamine. The administration of ketamine is not associated with increased intracranial pressure if normocapnia is achieved, making it possible anesthetic for neurosurgery. The other areas to explore include the role of ketamine to prevent opioid-induced acute tolerance and treat major depressive disorder.